Deadwood Diversity of Boreal and Sub-boreal Old-growth Forests in Southern Finland - Isabella De Meo; Roberta Pastorelli; Francesko Vitali; Alessandro Paletto (South-East European Forestry)
In the last century, old-growth forests in boreal and sub-boreal zone have decreased, along with their contribution to biological diversity. In order to carry on management strategies aimed at maintaining deadwood diversity in old-growth forests, it is fundamental to identify simply and readily measurable indicators. This study investigated the deadwood diversity in four old-growth forests in southern Finland. Five indicators of deadwood diversity (deadwood amount and diversity by species, component, decay class, water reservoir in logs) were estimated and analysed. The results showed an average deadwood volume of approximately 85±28 m3·ha−1 diversified by decay class and component. Besides, the results showed average Shannon index values four the four old-growth forests equal to 0.488 for deadwood species diversity, 0.932 for component diversity, and 1.286 for decay class diversity. The set of deadwood diversity indicators used in this study successfully supported the analysis of deadwood diversity in boreal and sub-boreal old-growth forests.